Association between -174G>C polymorphism in the IL-6 promoter region and the risk of obesity: A meta-analysis. Issue 33 (August 2018) - Hu, Man; Yu, Zhaomin; Luo, Dan; Zhang, Haiming; Li, Jinxiao; Liang, Fengxia; Chen, Rui
Abstract: Background: Many researchers have suggested that the -174G>C polymorphism in the interleukin-6 (IL-6) promoter region contributes to the risk of obesity; however, this hypothesis is still inconclusive. Therefore, we conducted a meta-analysis to combine the data from several studies to arrive at a conclusion regarding the association between -174G>C polymorphism and the risk of obesity. Methods: The PubMed and Embase databases were searched up to February 20, 2018. The odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated using a random-effects model. Subgroup analysis and sensitivity were also performed. Results: Ten eligible studies involving 7210 cases were performed to identify the association strength. The association strength was measured by the ORs and 95% CIs. By pooling the eligible studies, we found a significant association between the -174G>C polymorphism and obesity risk (C vs G: OR = 1.37; 95% CI, 1.08–1.74; P heterogeneity < .01). Overall, individuals with the variant CC (OR = 1.58; 95% CI, 1.09–2.28; P heterogeneity < 0.01) and GC/CC (OR = 1.61; 95% CI, 1.13–2.29; P heterogeneity < .01) were associated with a significantly increased risk of obesity. Conclusion: The meta-analysis results suggested that the polymorphism -174G>C in the IL-6 promoter region was associated with a significantly increased risk of obesity.